EVALUASI TINGKAT KEPATUHAN MINUM OBAT PASIEN HIPERTENSI DI PUSKESMAS KENJERAN MENGGUNAKAN METODE MMAS-8 - Ana Khusnul Faizah; Jala Kesit Dewayani; Angelica Kresnamurti (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
Adherence is an important factor in controlling blood pressure in hypertensive patients. This study aimed to evaluate the level of medication adherence in hypertensive patients at the Kenjeran Health Center. The research method used was observational analysis with a cross-sectional design and evaluation through a questionnaire to measure the level of adherence and the MMAS-8 questionnaire to measure medication adherence. The results obtained for the level of medication adherence based on the MMAS-8 method showed that 52 patients (64%) were in the low MMAS-8 adherence category, 21 patients (26%) were in the moderate MMAS-8 adherence category, and 8 patients (10%) included in the high MMAS-8 compliance category. The conclusion of this study is that the level of adherence to medication use in hypertensive patients at the Kenjeran Health Center is at low adherence.